2019
DOI: 10.18332/tid/112154
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with smoking cessation and relapse in the Japanese smoking cessation treatment program: A prospective cohort study based on financial support in Suita City, Japan

Abstract: INTRODUCTIONThe purpose of this study is to clarify the effect of providing financial support and factors associated with smoking cessation and relapse in the Japanese smoking cessation treatment (SCT) program based on financial support.METHODSA prospective cohort study was conducted at the smoking cessation outpatients of hospitals or clinics in Suita City, Japan from May 2017 to September 2018. In all, 153 participants were recruited and received standardized treatment based on the SCT program. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Consistent with our findings, previous studies have shown that the level of confidence in succeeding to quit is an important factor, also indicative of the success [ 27 , 28 ]. Quitters at Wave 2 also planned to quit at Wave 1, although levels of desire to quit were low.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our findings, previous studies have shown that the level of confidence in succeeding to quit is an important factor, also indicative of the success [ 27 , 28 ]. Quitters at Wave 2 also planned to quit at Wave 1, although levels of desire to quit were low.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis also showed that higher education and household income are associated with quitting, which aligns with previous research [ 33 , 34 , 35 ]. In addition, our findings concerning lighter smoking and low levels of perceived addiction among those who quit [ 36 , 37 , 38 ] as well as the presence of a disease [ 10 , 27 , 39 ] or health concerns about smoking [ 10 , 40 , 41 ] are consistent with the literature. Others have found that suffering from a chronic disease or multiple comorbidities caused or worsened by smoking do not always lead to cessation [ 42 ], which was true for some of our study’s respondents.…”
Section: Discussionsupporting
confidence: 89%
“…[43,44] In a cohort study conducted in Japan, smoking cessation success rates were higher in those with family members living together. [45] Similarly, in a longitudinal study conducted in the United States, smoking relapse rates were also reported to be lower in the presence of family members living with them. [18] In addition, the long-term smoking cessation rate has been reported to significantly increase when the spouse is a nonsmoker.…”
Section: Discussionmentioning
confidence: 96%